Territorial Infraestructure, Economy and International Business in Colombia - Gutiérrez Ossa, Jahir (Cuadernos de Administración, 2009)
The constant claims related to the lack of physical and logistical, particularly multimodal infrastructure (routes, ports, airports and networks of interconnected transport) required for the economic development of the country, are forcing consideration of this theme as a corporeal parameter, and not an exogenous one to the companies and of the territory. So far, it has been one of the most contested elements for its impact on the productive and competitive capacity for the opening of international trade with Colombia. In the face of this, it is necessary to do a review of the contribution that it generates for an economy counting on a good and efficient infrastructure equal to the conditions of production and access to the international markets, and especially the territories, as is the case of various regions of the country who aim for such a point of view. Internalizing such variables will allow realization of the adjustments the country needs in such themes and in particular how much of a relationship should exist between the territorial productive conditions with respect to the developments in infrastructure and the scope of both in face of international commercial possibilities. This article is a product from the perspective of the International Business of a research project called "Economic spatial impact of the projects of physical and geographical infrastructure in Antioquia State (Colombia).” PHASE 1: Urabá’s Port and PHASE 2: complementary Geo-infrastructure", in agreement between the University of Medellin, the institution ESUMER (Escuela Superior de Mercadeo) of Medellin and the company of analysis georreferencial INFOMAPAS in Medellin